NUMERICAL SOLUTION FOR VOLTERRA-FREDHOLMINTEGRAL EQUATION OF THE SECOND KINDBY USING LEAST SQUARES TECHNIQUE - Ahmed, Shazad (Iraqi Journal of Science, 2024)
In this paper we investigate the numerical solution of an important class ofmixed linear integral equations, called Volterra-Fredholm integral equations whichare used in technology, mechanics and mathematical physics.The basic concepts are: First, approximates the unknown function by a tensorproduct (Algebraic or Chebyshev)-surface and substituting it in the Volterra-Fredholm integral equations. Second, apply least-square technique for minimizingthe error terms on the given domain. Third, obtain a system of linear algebraequations which we solve for control points.An algorithm is illustrated by several numerical examples with comparison tablesand written computer programs in MatLab (V 7.1) for the given algorithm.